2005
DOI: 10.1107/s0907444905001216
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of AFM and X-ray diffraction to analyze crystals of an engineered, domain-deleted antibody

Abstract: A genetically engineered humanized C H 2-domain-deleted monoclonal antibody lacking any interchain-hinge disulfide bonds has been crystallized in the presence of detergent in a form suitable for X-ray diffraction analysis. The crystals were grown from 4 M formate along with Triton X-100 and had P2 1 2 1 2 space-group symmetry, with unit-cell parameters a = 83, b = 224, c = 167 Å . The crystals diffract to beyond 2.8 Å resolution. A disordered crystal form of larger size and more attractive habit was also grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, the AFM is suitable to complement the structural information of proteins obtained, e.g. by X‐ray diffraction analysis (18). Moreover, the imaging of complex biological structures like the surface of single living cells in nanometer resolution is also reported (19).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the AFM is suitable to complement the structural information of proteins obtained, e.g. by X‐ray diffraction analysis (18). Moreover, the imaging of complex biological structures like the surface of single living cells in nanometer resolution is also reported (19).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that one of the most harmful impurities which limits crystal quality consists of molecules exhibiting structural variability, including clusters or aggregates (McPherson et al, 2004). In this sense, it is noteworthy that an interesting case studied by AFM has been reported in which competition between different oligomeric forms might be responsible for the disorder and low resolution limit of the diffraction patterns (Larson et al, 2005). In the present study, the information obtained from the AFM analysis, although limited, helps us to understand the most probable reason for the relatively poor diffraction properties of the HSP17.9 crystals.…”
Section: Microscopic Analysismentioning
confidence: 99%
“…Details of the crystallization of HuCC49DCH2 form B have been described elsewhere, along with an atomic force microscopy investigation of the crystals. 9 The crystals used for diffraction analysis were grown by vapor-diffusion at 17 8C from 4 M sodium formate (pH 7.2) in the presence of 1.5 mM Triton X-100. Detergent was essential to crystallization, and many detergents were effective in yielding crystals, but, so far, only Triton X-100 produced ordered crystals that diffract to adequate resolution.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence from AFM studies of HuCC49DCH2 and its crystals that, under the crystallization conditions noted above, tetrameric assemblies are present in solution, and that crystal growth proceeds through the incorporation of tetramers into the crystal lattice. 9 In contrast to the ring-to-ring interface discussed above, there are only six contacts (interatomic distances !4 Å ) between tetramers along the a axis and a total of only 463 Å 2 of buried surface area per ring assembly.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation